Rammang-Rammang di Kabupaten Maros, Tiga Langkah Strategis Pengelolaan Pariwisata Berbasis Alam Yang Berkelanjutan (Jurnal Ilmiah Pariwisata, 2015)
High expectation comes from different stakeholders in South Sulawesi province that tourism should provide more benefits to the economic prosperity of the community and to the preservation efforts of tourism resources. This is particularly reflected in Rammang-Rammang, Maros regency where its establishment as tourism attraction since the last two years has attracted tourists to explore the beauty of nature combined with rural-based tourism. This paper seeks to recommend how a nature-based tourism attraction should be managed based on the principles of sustainable tourism. Three strategic approaches are recommended and discussed by integrating the theoretical approaches of sustainable tourism and the phenomena in Rammang-Rammang. A qualitative approach has guided the researcher in understanding the conduct of sustainable tourism. This paper suggests that although Rammang-Rammang is a new tourism attraction, tourism stakeholders are required to work together to really support the protection and the preservation of natural environment as well as to encourage balanced and active participation by the local people through creative efforts.